2023
DOI: 10.3390/biomedicines11092413
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Relationship between the Immune Response, Inflammation, Oxidative Stress, and the Pathogenesis of Sickle Cell Anaemia

Florence Ifechukwude Aboderin,
Taofeeq Oduola,
Glenda Mary Davison
et al.

Abstract: Sickle cell anaemia (SCD) is a life-threatening haematological disorder which is predominant in sub-Saharan Africa and is triggered by a genetic mutation of the β-chain haemoglobin gene resulting in the substitution of glutamic acid with valine. This mutation leads to the production of an abnormal haemoglobin molecule called haemoglobin S (HbS). When deoxygenated, haemoglobin S (HbS) polymerises and results in a sickle-shaped red blood cell which is rigid and has a significantly shortened life span. Various re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 130 publications
(250 reference statements)
0
3
0
Order By: Relevance
“…Several reviews have revealed a solid connection between oxidative stress, inflammation, the immune response, and the pathogenesis of SCD, enhancing the role of the dominant natural immune system [ 205 , 206 ].…”
Section: Nutritional Perspectives In Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have revealed a solid connection between oxidative stress, inflammation, the immune response, and the pathogenesis of SCD, enhancing the role of the dominant natural immune system [ 205 , 206 ].…”
Section: Nutritional Perspectives In Sickle Cell Diseasementioning
confidence: 99%
“…Substantial oxidative stress is a prominent contributor to SCD due to a disproportionate yield of reactive oxygen species compared with the ability of antioxidant agents, including enzymes such as SODs, catalase, and glutathione peroxidase, to counteract them. Multiple inflammatory pathways are stimulated in a chain reaction involving sickle cell redox balance, hemolysis, vasculopathy, and regulation in the immune response [ 205 ].…”
Section: Nutritional Perspectives In Sickle Cell Diseasementioning
confidence: 99%
“…The precursors decrease the expression of the EPO receptor, hence impeding the generation of EPO [53]. Furthermore, IL-1 and other proinflammatory cytokines have been linked to the activation of macrophages for erythrophagocytosis, which causes the early erythrocyte destruction and reduced erythrocyte survival [54].…”
Section: Specific Actions Of Proinflammatory Cytokinesmentioning
confidence: 99%
“…Additionally, oxidative modifications in sickle RBCs, caused by oxidants like nitric oxide (NO•) and ONOO − released during hemolysis, lead to further complications including vaso-occlusion, renal damage, and continued hemolysis ( Nader et al, 2020 , Jutant et al, 2021 , Wang and Zennadi, 2021 , Aboderin et al, 2023 ).…”
Section: Ferroptosis – Vaso-occlusion and Hemolysis In Scdmentioning
confidence: 99%